Diet of Moenkhausia bonita (Benine, Castro & Sabino 2004) (Characiformes: Characidae) in streams in the basin of rio Formoso, Brazilian Midwest - Caldatto, Amanda Menegante; Dias, Rosa Maria; Ferreira, Anderson (Biota Neotropica, 2023)
Abstract To characterize the diet composition of Moenkhausia bonita and its temporal and ontogenetic variations in streams in the Formoso River basin (MS). The collections were carried out in seven sampling points in two periods throughout the year (dry and rainy). The food items were analyzed according to the volumetric and occurrence frequency methods and the diet was characterized through the Food Index (IAi%). To determine ontogeny, the specimens were divided into five size classes in the dry (D1 to D5) and rainy (R1 to R5) periods. To verify the difference between the species’ diet between the size classes and the periods of the year, the Permutational Multivariate Analysis of Variance – PERMANOVA analysis was performed. Moenkhausia bonita was classified as an invertivore when it consumed basically both aquatic and terrestrial invertebrates (99.5% of the diet), with higher consumption of aquatic invertebrates. There was a significant difference in the diet of between the dry and rainy periods, and although the species basically consumed the same items in the two studied periods, the proportions were different and there was no difference in the diet between size classes. M. bonita diet is based on autochthonous resources regardless of the size class, but that there were different consumption patterns when comparing the different periods of the year. The present study provided the first information on the feeding of M. bonita in a lotic environment and diet spectrum in the developmental phases, (ontogeny) and periods of the year, enabling a better understanding of the species, the importance of invertebrates in its diet, and the need for future studies on the biology, autoecology, and behavior of this species. Resumo Caracterizar a composição alimentar de Moenkhausia bonita e as variações temporais e ontogenéticas na dieta desta espécie em riachos da bacia do rio Formoso (MS). As coletas foram realizadas em sete pontos amostrais em dois períodos do ano (seco e chuvoso). Os itens alimentares foram analisados de acordo com os métodos volumétrico e de frequência de ocorrência e a dieta foi caracterizada através do Índice Alimentar (IAi%). Para determinar a ontogenia, os espécimes foram divididos em cinco classes de tamanho nos períodos seco (D1 a D5) e chuvoso (R1 a R5). Para verificar a diferença entre a dieta da espécie entre as classes de tamanho e os períodos do ano foi realizado a Análise de Variância Multivariada Permutacional – PERMANOVA. M. bonita foi classificada como invertívora ao consumir basicamente invertebrados tanto aquáticos quanto terrestres (99,5% da dieta), com consumo maior de invertebrados aquáticos. Houve diferença significativa na dieta entre os períodos seco e chuvoso, apesar da espécie consumir basicamente os mesmos itens nos dois períodos estudados, as proporções foram distintas e não houve diferença na dieta entre as classes de tamanho. A dieta de M. bonita é baseada em recursos autóctones independente da classe de tamanho, mas que houve consumo diferente entre os períodos do ano. O presente estudo forneceu as primeiras informações sobre a alimentação de M. bonita em ambiente lótico e seu espectro alimentar nas fases de desenvolvimento(ontogenia)e períodos do ano, possibilitando melhor conhecimento da espécie, a importância dos invertebrados em sua dieta e a necessidade de estudos futuros sobre a biologia, autoecologia e comportamento desta espécie.